2021
DOI: 10.1039/d1ra04868f
|View full text |Cite
|
Sign up to set email alerts
|

In situ microwave heating fabrication of copper nanoparticles inside cotton fiber using pressurization in immiscible liquids with raw material solutions

Abstract: Copper nanoparticles were created inside of cotton fibers by pressuring immiscible liquids against raw material solutions and applying microwave heating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Moreover, the special lines in the textile industry can be counted as another class of textile attributes. For example, the pad-dry-cure lines in the traditional finishing processes are very suitable for developing antiviral fabrics, because of their accessibilities for large-scale production. In contrast, despite a large number of antiviral nanofibers being prepared using the electrospinning technique on a laboratory scale, a large amount of commercial supply still faces great challenges.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Moreover, the special lines in the textile industry can be counted as another class of textile attributes. For example, the pad-dry-cure lines in the traditional finishing processes are very suitable for developing antiviral fabrics, because of their accessibilities for large-scale production. In contrast, despite a large number of antiviral nanofibers being prepared using the electrospinning technique on a laboratory scale, a large amount of commercial supply still faces great challenges.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A type of cotton fibers that contains Cu NPs possesses anti-influenza A virus properties. It was revealed that the antiviral activity values of the produced fibers were more than the value of reference 3.0, which suggests a high antiviral characteristic (Miyakawa et al, 2021). Li et al combined the antimicrobial properties of Cu and chlorine dioxide into polymeric micelle formulations (Li et al, 2018).…”
Section: Surface Coatingmentioning
confidence: 99%
“…Copper nanoparticles were formed inside cotton fibers by in situ microwave heating with antiviral properties against influenza A virus, but their durability needs to be further improved. 22 sition technologies, 23 solution-based technologies, 24 autocatalytic electroless deposition, 25 and polymer-assisted electroless deposition 26 ) show great potential for developing conductive fibers, these metal coatings suffer from poor adhesion, shortterm environmental stability, and failure to achieve flame retardance in harsh conditions. 27 In principle, cellulose derived from vegetation has the advantages of renewability, inherent biocompatibility, and degradability, which are widely used in textile, food, pharmaceutical, and biomedical device industries.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Li et al constructed biomimetic sensors by the layer-by-layer method with graphene sheaths on spidroin fibers but with low electrical conductivity (95.3 S m –1 ). Copper nanoparticles were formed inside cotton fibers by in situ microwave heating with antiviral properties against influenza A virus, but their durability needs to be further improved . Although metallization methods (vacuum deposition technologies, solution-based technologies, autocatalytic electroless deposition, and polymer-assisted electroless deposition) show great potential for developing conductive fibers, these metal coatings suffer from poor adhesion, short-term environmental stability, and failure to achieve flame retardance in harsh conditions …”
Section: Introductionmentioning
confidence: 99%